2017
DOI: 10.1891/1541-6577.31.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation in Chronic Disease Populations: An Integrative Review

Abstract: Background and Purpose Emotion regulation, the experiencing, processing, and modulating of emotional response, is necessary to manage the emotional stressors common in patients with chronic illness. Overwhelming emotional demands deplete the resources needed for everyday self-care management of chronic disease, contributing to poor health outcomes. Emotion regulation is shown to impact behaviors in healthy individuals, yet a review of literature examining evidence of associations in chronically ill populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 40 publications
2
47
1
1
Order By: Relevance
“…Our metasynthesis showed that important themes raised by the participants, namely acceptance of the condition, increased emotion-regulation skills and reduced feelings of isolation, were only marginally represented in the quantitative outcome measures. Being diagnosed with a long-term physical condition does indeed entail an increased risk for higher depression and anxiety (Clarke & Currie, 2009;Patten, 2001), but it can also involve acceptance of and coping with the condition (Ambrosio et al, 2015), isolation (Ohman, Soderberg, & Lundman, 2003), self-blame (Callebaut, Molyneux, & Alexander, 2017) and emotion-regulation (Wierenga, Lehto, & Given, 2017) and it may be important to measure these outcomes. Furthermore, compassion-based interventions target both mental health difficulties and mental health resources (Bohlmeijer & Westerhof, in press), yet resources such as mental well-being (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our metasynthesis showed that important themes raised by the participants, namely acceptance of the condition, increased emotion-regulation skills and reduced feelings of isolation, were only marginally represented in the quantitative outcome measures. Being diagnosed with a long-term physical condition does indeed entail an increased risk for higher depression and anxiety (Clarke & Currie, 2009;Patten, 2001), but it can also involve acceptance of and coping with the condition (Ambrosio et al, 2015), isolation (Ohman, Soderberg, & Lundman, 2003), self-blame (Callebaut, Molyneux, & Alexander, 2017) and emotion-regulation (Wierenga, Lehto, & Given, 2017) and it may be important to measure these outcomes. Furthermore, compassion-based interventions target both mental health difficulties and mental health resources (Bohlmeijer & Westerhof, in press), yet resources such as mental well-being (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on the ER in chronical illness are still at the beginning and scarce in number. Among these studies, only a few are assessing the role of expressive suppression and cognitive reappraisal mechanisms (Wierenga et al, 2017). As far as we know, the present study is the first to investigate, in a multidimensional assessment, the expressive suppression mechanism in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Participants expressed intense demands on emotional support. [39][40][41] Health professionals are expected more to value empathy, understanding, and reassurance on what patients are suffering because they are trained to be so. 42,43 Offered with peers' experiences, patients could absorb practical knowledge from peers to meet their own self-management needs.…”
Section: Discussionmentioning
confidence: 99%